Origami folded surfaces: kinetic system behind the folding - Osório, F.; Oliveira, S. (Kine[SIS]tem - From Nature to Architectural Matter Conference Proceedings, 2017)
“Today’s intensification of social and urban change, coupled with the responsibility of issues of sustainability, amplifies the demand for interactive architectural solutions. In the context of architectural need, the attribute of being able to adapt to changing needs is paramount in contemporary society.” (Fox and Kemp, 2009). Since the 1960’s that Architecture is progressively more merged with several other fields. Fields like biology, robotics, mechanics, electronics, parametric design, digital fabrication and so many others get to be together through Architecture. It is getting easier and more feasible for the designer to create buildings that are kinetic, interactive and/or responsive in order to communicate with users, enhance the building’s performance in response to changing atmospheric conditions and even transform its own geometry to reconfigure spaces as a functional answer to changing demands. The use of kinetic buildings, or kinetic elements in a building is becoming a natural response to concrete architecture solutions in order to make buildings “intelligent” and “alive” so they can meet the actual demands of users and use the technological means that are currently available. On this sense this paper focuses specifically on kinetic architectural systems through the use of Rigid Origami Surfaces. Their geometry gives them elastic capacities and is versatile enough to be used in a wide set of systems.